Designing molecular solids with structural control and tunable physical properties using co-crystallization techniques - Panikkattu, Sheelu (Kansas State University, 2013)
Physical properties of bulk solids are typically governed by the molecular arrangement of individual building blocks with respect to each other in the crystal lattice. Thus the ability to synthesize molecular crystals with pre-organized connectivities allows for the rational design of functional solids with desirable and tunable physical properties. A thorough understanding of the various intermolecular interactions that govern the solid-state architectures is an important pre-requisite for the rational design of molecular solids. In order to understand the role of molecular geometric complementarity in the design of solid-state architectures, we explored the structural landscape of two isomeric pyridine based acceptors (3N and 4N) with binding sites oriented along different directions, i.e. parallel and at angle of 60° respectively, with a series of even chain diacid (colinear binding sites) and odd chain diacid (binding sites oriented along 120°) using co-crystallization technique. The results obtained shows a striking correlation between the observed solid state architecture and geometric complementarity of interacting species. Combinations of 3N with odd and 4N with even chain diacid produced 1-D chains whereas 3N with even and 4N with odd chain diacid generated 0-D ring architectures. In order to exploit the possibility of fine-tuning physical properties using co-crystallization techniques, solubility measurements were performed on 3N and 4N co-crystals with the diacids. The results show that the solubilities of 3N and 4N in the co-crystal form were very different from their solubility in the pure form. Also, there was a strong correlation observed between the solubility of the co-crystals and their corresponding co-formers, i.e. diacids. To explore the dependence of crystal structure on a physical property such as melting point, we synthesized co-crystals of 3,3‟-azopyridine and 4,4‟-azopyridine with a series of even chain diacids. Structural consistency was obtained within the two groups of co-crystals. In both groups, 1-D chains were formed with the diacid as the primary building block. However, In the series of 3,3‟-azopyridine co-crystals, the co-crystal with succinic acid showed a different solid-state packing arrangement (although the primary building block was same as others) compared to the others in the same series. This difference is also reflected as a deviation in the melting point, while the others in the series showed a perfect correlation between the structural consistency and melting point behavior. It was also observed that the co-crystals of 4,4‟-azopyridine displayed higher melting points than co-crystals of 3,3‟-azopyridine which could be due to the differences in the overall packing of the crystal which is a combination of different intermolecular interactions that exist between molecules in the solid state. Using bi-functional donors (with both hydrogen and halogen bond donors on same backbone), we investigated the relative strengths of hydrogen and halogen bond donors in the presence of two isomeric acceptors, 3,3‟-azopyridine and 4,4‟-azopyridine, which exhibit geometric bias in their binding-site orientation. Based on the crystal structures, we noticed a preferential binding of hydrogen bond donors with 3,3‟-azopyridine and both hydrogen and halogen bond donors with 4,4‟-azopyridine. This shows that the two types of donors are very comparable and their binding preference is governed by the geometric complementarity between the donor-acceptor pair. Finally, we explored the scope of using co-crystallization for tuning the physical properties of two agrochemicals, cyprodinil and terbuthylazine. The crystal structures of the actives with a series of even chain diacids displayed structural consistency in the primary motifs within the two groups, while few differences were observed in the packing arrangement and secondary interactions. By forming co-crystals we were able to improve the solubility and melting point of cyprodinil, while ensuring that the hygroscopicity of the active was unaltered.
Keywords: Cocrystals; Chemistry (0485)